AEROSOLS OBSERVATIONS WITH A NEW LIDAR STATION IN PUNTA ARENAS, CHILE - Barja Gonzalez, Boris; Zamorano Banda, Felix De La Cruz; Ristori, Pablo; Otero, Lidia; Quel, Eduardo; Sugimoto, Nobuo; Shimizu, Atsushi; Santana, Jorge (My University, 2018)
A tropospheric lidar system was installed in Punta Arenas, Chile (53.13 S, 70.88 W) in September 2016 under the collaboration project SAVERNET (Chile, Japan and Argentina) to monitor the atmosphere. Statistical analyses of the clouds and aerosols behavior and some cases of dust detected with lidar, at these high southern latitude and cold environment regions during three months (austral spring) are discussed using information from satellite, modelling and solar radiation ground measurements.
Keywords: None